Edge effects on carabid beetles (Coleoptera: Carabidae) between forest fragments and agricultural fields in south-east Brazil - Cividanes, Francisco J. [UNESP]; Santos-Cividanes, Terezinha M. dos; Ferraudo, Antonio S. [UNESP]; Matta, Danilo H. da [UNESP] (Wiley-Blackwell, 2018)
There is very little information available on the abundance, diversity and distribution of Neotropical species of carabid beetles in agroecosystems. We studied the diversity and similarity of carabids in forest fragments, soybean/corn crops and edges, and we also determined the number of individuals of carabid species in fragment and crop during the growing season of crop and the off-season period. The study was carried out on three separate areas located in the Jaboticabal and Guaira municipalities, Sao Paulo State, Brazil, from November 2004 to May 2008. Each location consisted of forest fragment, adjacent soybean/corn crop and edge. Carabids were sampled with 48 pitfall traps arranged along two parallel transects 200 m long. In total, 3544 individuals of 62 species were collected, with the following five species dominating: Abaris basistriata Chaudoir, Odontocheila nodicornis (Dejean), Tetracha brasiliensis (Kirby), Scarites sp. 3 and Scarites sp. 4. Highest species diversity occurred in the edge with weedy plants. Carabid communities showed high similarity between edge - crop and edge fragments. Abaris basistriata, Calosoma granulatum Perty, Galerita brasiliensis Dejean, Selenophorus alternans Dejean, Selenophorus discopunctatus Dejean, T. brasiliensis and species of Scarites showed the most potential as biocontrol agents of soybean/corn pests.
Keywords: biological control; diversity; Glycine max; ground beetle; weed; Zea mays